2019
DOI: 10.30772/qjes.v12i2.601
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical removal of copper from a simulated wastewater using a rotating tubular packed bed of woven screens electrode Removal of heavy metals using packed bed rotating electrode

Abstract: Rotating cylinder electrodeWoven screens Copper removalResponse surface methodology A B S T R A C T Copper removal from simulated wastewater was investigated by using a rotating tubular packed bed of woven screens electrode as a cathode in a new design of the electrochemical reactor. The effects of electrolysis operating parameters like current (0.5-2.5 A), rotation speed (150-750 rpm), and initial copper concentration (100-500ppm) were investigated. Optimization of process parameters was carried out by adopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Electrolytic recovery is used in the wastes from plating and metal finishing. Also, used in the electronics and printed circuit board for the removal and/or recovery of metals in solution [30,[35][36][37]. By utilizing insoluble anodes during electrowinning, various metals that are found in industrial wastewaters can be electro recovered [38 -49].…”
Section: Environmental Electrochemistry and Electrochemical Techniquesmentioning
confidence: 99%
“…Electrolytic recovery is used in the wastes from plating and metal finishing. Also, used in the electronics and printed circuit board for the removal and/or recovery of metals in solution [30,[35][36][37]. By utilizing insoluble anodes during electrowinning, various metals that are found in industrial wastewaters can be electro recovered [38 -49].…”
Section: Environmental Electrochemistry and Electrochemical Techniquesmentioning
confidence: 99%
“…Indeed using pH value higher than 2 will give higher removal of copper by electrodeposition. However, it is difficult to use pH higher than 2 since copper could be precipitated as hydroxide if the solution pH is greater than 2 as approved by theoretical solubility of copper hydroxide diagram All runs were proceeded at current of 1.5 A, rotation speed of 450 rpm, and total initial concentration of 300 ppm The selected values of these operation variables represent the midpoint of the studied range of these variables in the Box-Behnken experimental design adopted in our previous work for copper removal using this rotating electrode where copper removal efficiency higher than 97% was obtained [33]. Our previous results showed that using current higher than 1.5 A resulted in a slightly increase in removal efficiency with a large drops in current efficiency.…”
Section: Experimental Workmentioning
confidence: 99%
“…The goal of RSM is to estimate the relative impact of various parameters and finally to achieve the best operating conditions by optimizing this response Thirugnanasambandham et al [31]. In our previous work, we studied the removal of copper utilizing a tubular packed bed woven screens electrode, where a good performance of this design had been reported Hemeidan and Abbar [32]. The main purpose of the work underway is to evaluate the efficiency of this design in the removal of cadmium by optimizing process parameters like initial metal concentration, current, rotational speed, and pH so as to achieve larger removal efficiency as possible as in cadmium removal from simulated synthetic wastewater.…”
Section: Introductionmentioning
confidence: 99%